Quality Management Strategy Based on Total Quality Management (TQM) Ibtidaiyah Madrasah Tahfiz El Muna Q Krapyak Yogyakarta - Muhammad Irfai Muslim; Ahmad Syafii (Nusantara: Jurnal Pendidikan Indonesia, 2022)
The issue of low and unsatisfactory service quality has prompted the public sector to carry out reforms in all fields. Various concepts, “ New Public Management,” which has proven its success in the private/business sector, are tried to be adopted and implemented. One of the quality management concepts widely applied in both the business and public sectors is TQM ( Total Quality Management). This study aims to explain the application of TQM-based quality management principles in MI Tahfidz El Muna Q (Madrasah Ibtidaiyah Tahfidz El Muna Q) Islamic boarding school Al-Munawwir Krapyak Yogyakarta. The type of research is qualitative research with a case study approach. Methods of collecting data by observation, interviews, and documentation. Data analysis using thematic analysis. Test the validity of the data using the triangulation test. The results show that MI Tahfidz El Muna Q has implemented the TQM principle with good. TQM-based quality management principles applied are quality assurance Institute, education/training carried out to improve the quality of elementary school M, customer-oriented, communication pattern, empowering educators and education staff, reporting to stakeholders, benchmarking against other institutions, understanding of the institution’s long-term goals, routine evaluation, and happiness. Based on these ten indicators, it can be understood that MI Tahfidz El Muna Q has carried out continuous improvement well.